Physical activity for people with disabilities: Physical Activity Guidelines for Brazilian Population - Orcioli-Silva, Diego (2021)
Aiming to guide the population of the physical activity benefits to health, national researchers, in partnership with the Health Ministry, have elaborated the Physical Activity Guide for the Brazilian population. The aim of this study was to present the process of elaborating Brazilian physical activity recommendations for people with disabilities (PWD). The process of elaborating specific recommendations for PWD has included the participation of nine researchers/professionals who held weekly meetings, systematic reviews, and focus groups with PWD, caregivers, healthcare managers, professionals, and researchers. In the systematic review, a total of 83 studies were included and reviewed. The focus groups were performed using an electronic form sent by e-mail to health professionals, managers, and researchers who worked with PWD and virtual focus groups, which were conducted in two moments: (a) with PWD, caregivers, and professionals; (b) with teachers and researchers on the theme. Based on the results of systematic reviews and focus groups, the physical activity recommendations for PWD were developed considering the minimum physical activity time according to age group, domains of physical activity, and recommendations for reducing sedentary behavior. Therefore, the present work presented recommendations for physical activity for PWD, which can be combined with public policies, environments, and opportunities for physical activity, becoming an essential strategy for the engagement of PWD in physical activities.